Peak nasal inspiratory flow measurement and visual analogue scale in a large adult population. (21st April 2019) - Ottaviano, Giancarlo; Pendolino, Alfonso Luca; Nardello, Ennio; Maculan, Pietro; Martini, Alessandro; Russo, Massimiliano; Lund, Valerie J.
Abstract : Objectives: Nasal obstruction is the most common symptom in nasal diseases. It can be evaluated objectively, that is by means of peak nasal inspiratory flow (PNIF) measures and/or subjectively by means of validated questionnaires. However, it has been reported that there is a lack of reliable correlation between subjective and objective measurements of nasal obstruction. The aim of the present study was to evaluate the correlation between PNIF measurements and the subjective sensation of nasal obstruction measured by means of a visual analogue scale (VAS) in a large population of consecutive rhinologic patients. Design: Prospective clinical study. Setting: Tertiary rhinological referral centre. Participant main outcome measures: A total of 641 consecutive subjects were enrolled. Visual analogue scale and PNIF were performed to assess nasal obstruction. Nasal septal deviation was classified according to Mladina classification, and its severity was assessed using three levels of severity. Results: Although weak, there was a significant negative correlation ( r  = −0.13, P  = 0.001) between PNIF and VAS. Dividing the population in those affected by nasal septal deviation (NSD) and those affected by chronic rhinosinusitis (CRS), a week negative correlation between PNIF and VAS was again confirmed in both groups ( r  = −0.208, P  = 0.006 for NSD and r  = −0.13, P  = 0.04 for CRS). Peak nasal inspiratory flow and VAS were also evaluated according to the grade of polyps and the type and level of septal deviation. Conclusions: Visual analogue scale and PNIF significantly correlated, although with a low degree, in a large population of rhinologic patients. Peak nasal inspiratory flow, being cheap and simple to use, could be a good candidate to assist clinicians dealing with "airway" diseases in their daily clinical practice in order to provide comprehensive information on nasal function. Peak nasal inspiratory flow can in fact give some important rough insights on VAS, but these measurements cannot be alternative to each other.